2023
DOI: 10.3390/foods12142733
|View full text |Cite
|
Sign up to set email alerts
|

Storage Quality Changes in Craft and Industrial Blueberry, Strawberry, Raspberry and Passion Fruit-Mango Sorbets

Abstract: Sorbets are a popular dessert, especially during hot summer days. They can also have health-promoting qualities, mainly due to the nutritional value of the fruit from which they are made. The production technology can also have an impact on the final nutritional quality of the sorbets. This paper presents a comparative assessment of the quality of industrial fruit sorbets and their craft analogs. Sorbets with the following flavors were selected for the research: blueberry, strawberry, raspberry, and passion fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…It was determined that the panelists gave the highest scores to the sherbet samples at the beginning of storage: color (8.05), smell (7.15), taste (7.95), and overall preference (7.77). Similar results were obtained by Aljaloud et al, who investigated the color, consistency, taste, odor, and overall preference properties of raspberry, blueberry, strawberry, and passion fruit-mango sherbets during a 6-month storage period, and they found that the products showed the best sensory properties was at the beginning storage . In this study, it was observed that there was a tendency for color, odor, taste, and general likability values to decrease with increasing storage time.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It was determined that the panelists gave the highest scores to the sherbet samples at the beginning of storage: color (8.05), smell (7.15), taste (7.95), and overall preference (7.77). Similar results were obtained by Aljaloud et al, who investigated the color, consistency, taste, odor, and overall preference properties of raspberry, blueberry, strawberry, and passion fruit-mango sherbets during a 6-month storage period, and they found that the products showed the best sensory properties was at the beginning storage . In this study, it was observed that there was a tendency for color, odor, taste, and general likability values to decrease with increasing storage time.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained by Aljaloud et al, who investigated the color, consistency, taste, odor, and overall preference properties of raspberry, blueberry, strawberry, and passion fruit-mango sherbets during a 6-month storage period, and they found that the products showed the best sensory properties was at the beginning storage. 55 In this study, it was observed that there was a tendency for color, odor, taste, and general likability values to decrease with increasing storage time. However, this decrease did not show a statistical difference, and the sherbet samples were still within the general acceptability limits on the 21st day.…”
Section: Resultsmentioning
confidence: 72%
“…After a 30-day storage period, it was discovered that the optimized poppy sherbet's color, smell, and taste results from the sensory study dramatically decreased when compared with the 0th-day sample (p < 0.05). Palka and Wilczy ńska (2023) determined that the organoleptic properties (overall preference, color, odor, taste, and consistency) of blueberry, strawberry, raspberry and passion fruit-mango sorbets decreased during storage [43] (similar results to those found in our study). Hipólito et al (2016) reported that, based on consumers' evaluation, there was little change in the acceptance of lemon, orange, melon, strawberry, and mango sorbets during storage at −18 • C for 21 days [44].…”
Section: Sensory Properties In the Storage Processsupporting
confidence: 89%
“…There are several considerations required for consumer acceptance of a food product. Moisture content contributes to the overall acceptance, particularly to the overall taste, texture and appearance at the time of producing the product and over the storage period [83]. For instance, the grittiness of ice creams or sorbets occurs due to poor manufacturing processes that result in the over-crystallization of solids and liquids, as well as lactose crystallization.…”
Section: Improvements In Product Acceptancementioning
confidence: 99%